1993
DOI: 10.1080/10589759308952804
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Modifications in High Strength Steel

Abstract: This paper reports on the application of micromagnctic inspection techniques to the evaluation of the surface condition of shot peened, high strength HP9430 steel. It is shown from the results that the modification of the surface condition resulting from different shot peening intensities can be detected from the amplitude of the micromagnetic signals emitted from the surface under alternating magnetic field excitation. It is further demonstrated that the production of residual stresses in the surface of a ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Suominen and Tiitto [17] compared the values of residual stress measured by X-ray diffraction (XRD) and MBN methods in various shot-peened steels. Jiles et al [18] concluded that the graph of MBN activity versus magnetic field strength gives valuable information to determine the shot-peening condition of HP9-4-30 steel. Jacob et al [19] observed that variations in the MBN measurement results are less than those of XRD measurements performed on nitrided, ground and shot-peened 32CD4 steels.…”
Section: Estimation Of Surface Residual Stresses Using the Magnetic Bmentioning
confidence: 99%
“…Suominen and Tiitto [17] compared the values of residual stress measured by X-ray diffraction (XRD) and MBN methods in various shot-peened steels. Jiles et al [18] concluded that the graph of MBN activity versus magnetic field strength gives valuable information to determine the shot-peening condition of HP9-4-30 steel. Jacob et al [19] observed that variations in the MBN measurement results are less than those of XRD measurements performed on nitrided, ground and shot-peened 32CD4 steels.…”
Section: Estimation Of Surface Residual Stresses Using the Magnetic Bmentioning
confidence: 99%
“…Intermittent crack movements in stressed ferromagnets can generate simultaneous magnetic and acoustic pulses [30,31]. Because of their refined stress sensitivity, these effects have been incorporated into several commercially available NDE instruments [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Magnetomechanical Effectsmentioning
confidence: 99%